Fish for nutritional security - Meenakumari, B (Indian Farming, 2015)
For thousand of years, fish has been an important part of the human diet. It plays a major role in human nutrition. Fish is a versatile, tasty and easy to prepare food. It is the diet of the poor fishermen, which meets most of their nutritional requirements. In recent years the link between fish oil and heart disease has been the subject of a number of scientific papers. Medical researches carried out detailed investigations and showed that those who ate fish once or twice per week were protected against coronary heart disease. An increase in fish in the diet results in marked reduction in blood cholesterol and triglyceride level.